Range of Motion Spherical Grip Affected the Upper Extremity Muscle Strength in Post Stroke Patients - Lutfi Wahyuni; Siti Kotijah; Catur Prasastia Lukita Dewi (Journal of Ners and Midwifery, 2022)
Stroke is a medical emergency. Post-stroke patients generally experience muscle weakness in the limbs, postural disturbances and muscle atrophy. The purpose of this study was to prove the effect of ROM Spherical Grip exercise on post-stroke patients. The type of the study was pre-experimental with one group pre-test-post-test design. The independent variable was Range Of Motion (ROM) Spherical Grip. The dependent variable was the degree of upper extremity muscle strength in post-stroke infarct patients who had hemiparesi. The sampling technique used a consecutive sampling technique. The sample was 33 respondents. The data were taken by measuring the muscle strength before and after being given the intervention. The instrument used an observation sheet for assessing muscle strength and manual muscle testing (MMT) physical examinations in post-stroke patients. The results of this study showed that most of the muscle strength before giving the Spherical Grip ROM exercise was Poor (there was movement but could not fight gravity) as many as 14 respondents (42.4%). After the intervention of the Spherical Grip ROM exercise, the muscle strength was mostly Fair (can move against gravity) as many as 19 respondents (57.6%). There is an increase in upper extremity muscle strength before and after being given ROM Spherical Grip exercise in post-stroke patients who experience hemiparesis. This showed that the Spherical Grip could improve the tone of those who experience weakness and if done continuously could increase muscle strength in post-stroke patients. It is hoped that with this research Spherical grip exercises can be used as one of the treatments for stroke patients who experience decreased upper extremity muscle strength and collaborate with physiotherapy also assisted by taking drugs according to doctor's advice.